Restoration of Power Systems with AC/DC Conversion Terminal at Receiving-End Considering Parallel Transmission Lines - Erbin ZANG; Xueping GU; Pengfei LI; Chao YANG; Shaoyan LI; Chen WU (Zhongguo dianli)
The path optimization method proposed in previous studies severely restricts the restoration of LCC-HVDC system. To overcome this weakness, this paper studies power system restoration with AC/DC conversion terminal at the receiving-end. In this paper, the characteristics of LCC-HVDC transmission systems under the condition of system restoration are analyzed. To ensure the efficiency and security of restoration, the system restoration optimization model considering parallel transmission lines is established by taking the ratio of total power generation and grid charging reactive power as the optimization goal. Then hybrid particle swarm optimization is adopted to solve the problem of power system restoration, which is characterized by various constraints. The effectiveness of the proposed method is demonstrated and validated by the optimization results on the modified IEEE 39-bus system and a practical power system in Southwest China.